Poultry production in hot climates [ - Daghir, N. J. [ (Nuhad Joseph)] , 1935- (Wallingford, Oxfordshire, UK : CABI, 2008)
Describes how the detrimental effects of heat stress can be reduced through the manipulation of housing, breeding, and nutrition and management. This book contains contributions on controlled-environment housing, waterfowl, and breeding fast-growing brolers.
1. Present status and future of the poultry industry industry in hot regions -- 2. Breeding for resistance to heat stress -- 3. Breeding for fast-growing, high-yield broilers for hot conditions -- 4. Behavioural, physiological, neuroendocrine and molesclar responses to heat stress -- 5. Poultry housing for hot climates -- 6. Nutrient requirements of poultry at high temperatures -- 7. Feedstuffs used in hot regions -- 8. Mycotoxins in poultry feeds -- 9. Broiler feeding and management in hot climates -- 10. Replacement pullet and layer feeding and management in hot climates -- 11. Breeder and hatchery management in hot climates -- 12. Waterfowl production in hot climates
Includes bibliographical references and index
Keywords: Poultry; Poultry industry; Poultry -- Climatic factors